Photoactivated Anticancer Activity of Cobalt(III) Complexes with Naturally Occurring Flavonoids Chrysin and Silibinin - Dutta J.; Bera A.; Upadhyay A.; Yadav A.K.; Banerjee S.; Sarkar T.; Hussain A. (My University, 2025)
Photoactive metal complexes of bioessential transition metal ions with natural chelators are gaining interest as photocytotoxic agents for cancer photodynamic therapy (PDT). We report six new cobalt(III) complexes with a mixed-ligand formulation [Co(B)2(L)](ClO4)2 (Co1–Co6), where B represents a N,N-donor α-diimine ligand, namely, phenanthroline (phen; Co1, Co2), dipyrido[3,2-d:2’,3’-f]quinoxaline (dpq; Co3, Co4), and dipyrido[3,2-a:2’,3’-c]phenazine (dppz; Co5, Co6), and L is the monoanionic form of the naturally occurring flavonoids chrysin (chry; Co1, Co3, Co5) and silibinin (sili; Co2, Co4, Co6). Complexes displayed a d-d absorption band within 500–700 nm and exhibited excellent dark and photostability in solution. Cytotoxicity studies indicated significant activity of Co5 and Co6 against cervical (HeLa) and lung (A549) cancer cells under visible light (400–700 nm) irradiation giving low micromolar IC50 values (2.3–3.4 μM, phototoxicity index~15–30). The complexes demonstrated notably low toxicity against normal HPL1D lung epithelial cells. Flow cytometry assay revealed an apoptotic mode of cell damage triggered by the complexes when irradiated. ROS generation assay indicated the involvement of singlet oxygen species in the cell death mechanism when irradiated with light. Overall, complexes Co5 and Co6 with coordinated dipyridophenazine and flavonoid ligands are potential candidates for cancer PDT applications. © 2024 Wiley-VCH GmbH.